Deletion in the OA1 gene in a family with congenital X linked nystagmus. Issue 9 (1st September 2001) - Preising, Markus; de Laak, Jean-Paul Op; Lorenz, Birgit
Abstract : AIMS: To elucidate the molecular genetic defect of X linked congenital nystagmus associated with macular hypoplasia in three white males of a three generation family with clear features of ocular albinism in only one of them. METHODS: A three generation family with congenital nystagmus following X linked inheritance, and associated with macular hypoplasia was clinically examined (three males and two obligate carriers). Flash VEP was performed to look for albino misrouting. DNA samples were subjected to PCR and subsequent analysis using SSCP for all exons of the OA1 gene. RT-PCR was performed on a mRNA preparation from a naevus from one patient. PCR products presenting divergent banding patterns in SSCP and from the RT-PCR were sequenced directly using cycle sequencing with fluorescent chain termination nucleotides and electrophoresis in a capillary sequencer. RESULTS: The index case (patient 1, IV.1) was diagnosed with X linked OA1 at the age of 3 months because of typical clinical features: congenital nystagmus, iris translucency, macular hypoplasia, fundus hypopigmentation, normal pigmentation of skin and hair, and typical carrier signs of OA1 in his mother and maternal grandmother. Pigmentation of the iris and fundus had increased at the last examination at age 4 years. Albino misrouting was present at this age. In the maternal uncle (III.3, 51 years) who also suffered from congenital nystagmus there was clear macular hypoplasia and stromal focal hypopigmentation of the iris but no iris translucency or fundus hypopigmentation. Patient 3 (II.3, 79 years, maternal uncle of patient III.3) had congenital nystagmus and was highly myopic. The fundus appearance was typical for excessive myopia including macular changes. The iris did not show any translucency. Molecular genetic analysis revealed a novel 14 bp deletion of the OA1 gene at nt816 in exon 6. The mutation abolishes four amino acids (Leu 253-Ile-Ile-Cys) and covers the splice site. Nucleotides 814/815 are used as a new splice donor thus producing a frame shift in codon 252 and a new stop codon at codon 259. CONCLUSIONS: Macular hypoplasia without clinically detectable hypopigmentation as the only sign of X linked OA1 has been reported occasionally in African-American, Japanese, and white patients. The present family shows absent hypopigmentation in two patients of a white family with a deletion in the OA1 gene. We propose a model of OA1 that allows increase of pigmentation with age. We hypothesise that macular hypoplasia in all forms of albinism depends on the extracellular DOPA level during embryogenesis, and that in OA1 postnatal normalisation of the extracellular DOPA level due to delayed distribution and membrane budding/fusion of melanosomes in melanocytes results in increasing pigmentation.